PENGARUH KUALITAS KEHIDUPAN KERJA TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN - Ruhyaningtias Ruhyaningtias; Iriani Indri Hapsari (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2013)
Abstract This study aims to determine the effect of the quality of working life on organizational commitment in employees especially employees in PT. Mutualplus Global Resources in December 2013. Measurement scales used in this study was: Quality of Work Life Walton, in Zin (2004), and Bellingham & Meek, in Mas'ud (2004). The organizational commitment scale adapted from Allen & Meyer measurements, in Zin (2004) and Mowday, Steers & Porter, in Mas'ud (2004). The samples used in this study was 60 employees of PT. Mutualplus Global Resources. The method used is quantitative research with using the research data collection techniques such as interviews, observation, and using a questionnaire. The data analysis technique used was a simple regression analysis using the statistical software program SPSS version 18.00. Based on the results of hypothesis testing concluded that the quality of work life and a positive significant effect on organizational commitment in employees the product moment correlation coefficient is 0,697. However, due to the categorization of the quality of work life and organizational commitment included in the category with each having the same number of proportion, amounting to 80%, it can be concluded that the quality of work life of employees quite fulfilled that commitment of employees have also not too strong or weak against the organization. Major variables influence the quality of working life on organizational commitment show correlation of 0,486 which means that the variable quality of work life affects the organizational commitment about 48,6 % and the remaining 51,4 % is influenced by other variables. Key Word : Organizational Commitment and Quality of Work Life